CACCI country profile Ecuador - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Ecuador has great climatic variability, due to its geological diversity and variety in altitude and terrain. The country has two seasons: rainy and dry. Ecuador faces a variety of climatic risks such as floods and landslides caused by the increase in annual rainfall during phenomena such as El Niño, as well as droughts that weaken soils and affect agricultural processes. Likewise, there are effects caused by rising sea levels, melting glaciers, and vulnerability of water sources. The sectors that generate the greatest emissions in the country are energy, land use, and agriculture, which are vital for social and economic development. It is important to highlight the efforts made by the country through public policies and other instruments focused on the fight against climate change, which are aligned with its constitution and international agreements. In this way, Ecuador has a bases and guidelines for the development of strategies with an interdisciplinary approach and considering all the actors.